Do you know Cyathea divergens (Cyatheaceae-Polypodiopsida)? - Lehnert, Marcus (Phytotaxa, 2014)
The Neotropical scaly tree fern Cyathea divergens is a paradigm of a variable species with a wide geographical range. Studies in herbaria and in the field reveal that C. divergens is less frequently collected and less variable than previously thought. A lot of records are based on fragmentary collections of similar species that have the characteristically long-stalked, triangular, pinnatisect pinnules and sparse to absent laminar indument in common, but differ in other characters. Their separation from C. divergens is easy if petiolar characters are considered and even possible if microscopic remnants of the fine scurf on the pinnules are studied. Cyathea tuerckheimii is given here species status, eliminating one variety of C. divergens, whereas C. divergens var. sipaliwiniana is newly described. Cyathea convergens, here newly described, also belongs to this group. The identification of Cyathea ×jurgensenii as a sterile hybrid between C. tuerckheimii and C. fulva reduces the confusion that exists in the separation of C. tuerckheimii from C. divergens and C. fulva. The typification of Cyathea kalbreyeri is corrected here. The type specimen of that species represents a previously unrecognized species, while the specimens known under that name are similar to the type of Cyathea gibbosa, which in turn currently denominates a species that has to be referred to as Cyathea farinosa. One synonym of C. gibbosa, C. surukunensis, may represent a hybrid.